Anatomy and biomechanics of the Lisfranc ligamentous complex: A systematic literature review. (15th April 2021) - Sripanich, Yantarat; Steadman, Jesse; Krähenbühl, Nicola; Rungprai, Chamnanni; Saltzman, Charles L.; Lenz, Amy L.; Barg, Alexej
Abstract: Lisfranc injuries are challenging to treat and can have a detrimental effect on active individuals. Over the past decade researchers have investigated methods for the reconstruction of the Lisfranc ligamentous complex (LLC) to preserve its functional stability and mobility. To aid in this innovation, this study presents the current understanding of the anatomical and biomechanical characteristics of the LLC through a systematic review. Three medical databases (PubMed, Scopus, and Embase) were searched from inception through July 2019. Original studies investigating the anatomy and/or biomechanical properties of the LLC were considered for inclusion. Data recorded from each study included: number of cadavers, number of feet, gender, laterality, age, type of specimen, measurement methods, reported ligamentous bundles, ligament origins and insertions, geometric characteristics, and biomechanical properties of the LLC. The Quality Appraisal for Cadaveric Studies (QUACS) scale was used to assess the methodologic quality of included articles. Eight cadaveric studies investigating the LLC were included out of 1204 screened articles. Most articles described the LLC as three distinct structures: the dorsal- (DLL), interosseous- (ILL), and plantar- (PLL) Lisfranc Ligaments. The ILL had the largest thickness and insertional area of osseous attachment. Biomechanically, the ILL also had the highest stiffness and resistance to load prior to failure when loaded parallel to its fiber orientation. Current knowledge of the anatomical and biomechanical properties of the LLC are presented and highlight its significant role of stabilizing the tarsometatarsal articulation. Appreciating the biomechanical characteristics of the ILL may improve clinical insight in managing LLC injuries.